High frenal attachment and its prevalence among children - A retrospective study - Angel Fastina Mary; Lavanya Govindaraju (Wolters Kluwer Medknow Publications, 2022)
The frenum is a narrow mucosa fold surrounded by muscle fibers that connect the lips to the alveolar mucosa and the periosteum beneath. Midline spacing, commonly called as diastema, recession, interference with prosthodontic therapy, and difficulty speaking are all symptoms of a high frenal attachment. Frenectomy is a surgical treatment that involves removing the aberrant frenal connection. The frenum is a connective tissue membrane that connects one mouth surface to the next. The purpose of this study is to see how popular high frenal attachment is among children who visit a university dentistry hospital. This was a retrospective investigation evaluating the prevalence of high frenal attachment in patients visiting a Chennai dental institution. From June 2019 to March 2021, 11278 patients visited a dental clinic.